Design and Development of a Regional News Application Using PHP and Android - Khushali Gajera; Kinjal Chondigala; Aditya Raj Singh; Dr Yassir Farooqui; Dr K Himabindu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Regional News App is a new smartphone application that aims to fill the gap in regional news reporting, especially in Gujarat. Current news websites are more inclined towards national and international news with little emphasis on local news that has a direct impact on the lives of people residing in Gujarat. The gap will be bridged by the app by providing hyper-local news and international updates to provide an even-balanced news experience to the users. The service provides highly personalized experience, enabling the users to build their news preference, receive notifications at the local level, and utilize interactive content like quizzes and discussions. In addition to that, there is an event calendar to alert the citizens to local events, fairs, and government schemes. Special scholarship page is added to provide opportunities for students at an academic level. Moreover, target advertisement feature assists localized industries to reach their target consumers properly, thus initiating economic growth. The application has been developed utilizing PHP as backend technology, MySQL database for storage, and frontend utilizing HTML, CSS, and JavaScript. With a mix of regional news and global news, interactive elements, and business content, Regional News App is an offline-capable, community-focused news app. AI-driven content recommendation, multi-language capability, and improved search capabilities will be incorporated as future work to further expand user experience.